Internet jurisdiction and choice of law legal practices in the EU, US and China - Wang, Faye Fangfei (Cambridge University Press, 2010)
Internet Jurisdiction and Choice of Law: Legal Practices in the EU, US and China takes a solutions to obstacles approach, examines the existing jurisdiction and choice of law rules and proposes the interpretation of those rules to the digital age. It discusses the need of the modernisation and harmonisation of private international law, compares current legislative frameworks in the EU, US, China, and suggests a series of ways to remove the obstacles of the determination of Internet jurisdiction and choice of law for cross-border electronic B2B and B2C contracts.